Micro methods and micro apparatus for chemical pathology with special reference to paediatrics. Issue 3 (May 1966) - Clayton, Barbara E.; Jenkins, P.
Abstract : This article describes methods and apparatus which permit the estimation of a particular substance without requiring more blood than can conveniently and safely be removed from a child by capillary puncture. No reference will be made to the use of methods on the Technicon Auto-Analyzer as that machine is not yet generally geared to paediatric work, although a few centres have made their own modifications to permit certain methods to be performed on capillary samples of blood.